2015
DOI: 10.1021/acscatal.5b01159
|View full text |Cite
|
Sign up to set email alerts
|

Common Pathways in Ethanolysis of Kraft Lignin to Platform Chemicals over Molybdenum-Based Catalysts

Abstract: One-pot complete catalytic ethanolysis of Kraft lignin into C6–C10 chemicals, that is, aliphatic alcohols, esters, phenols, benzyl alcohols, and arenes, is achieved with a batch reactor over a number of supported molybdenum-based catalysts at 553 K in pure ethanol under autogenous pressure of 10.6 MPa. Metallic molybdenum, its carbide, and nitride all show remarkable activity, with the carbide and metallic catalysts giving the higher overall yields: 1640 and 1390 mg/g lignin, respectively. The major phases com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 54 publications
4
129
1
Order By: Relevance
“…For example, ethyl esters of carboxylic acid can be generated by the esterification reaction between ethanol and lignin-derived intermediates, such as hexenuronic acid formed in Kraft pulping [33]. Furthermore, the alcohols and esters formation were also reported in our previous work and the works done with woody biomass and a copper-doped Mg/Al mixed-oxide catalyst [24,31,34,35]. However, it's hard to determine how much of C6 alcohols and C8-C10 esters are produced from Kraft lignin.…”
Section: Catalyst Characterizationmentioning
confidence: 54%
See 2 more Smart Citations
“…For example, ethyl esters of carboxylic acid can be generated by the esterification reaction between ethanol and lignin-derived intermediates, such as hexenuronic acid formed in Kraft pulping [33]. Furthermore, the alcohols and esters formation were also reported in our previous work and the works done with woody biomass and a copper-doped Mg/Al mixed-oxide catalyst [24,31,34,35]. However, it's hard to determine how much of C6 alcohols and C8-C10 esters are produced from Kraft lignin.…”
Section: Catalyst Characterizationmentioning
confidence: 54%
“…The new catalyst gave a much higher overall yield than those reported results with MoC1-x and Cu-MgAlOx catalysts, which implies a synergistic effect between the two materials. Compared to Cu-MgAlOx, a heterogeneous catalyst, MoC1-x/Cu-MgAlOx can form molybdenum ethoxide (Mo(OEt)5) during the reaction in ethanol as we previously reported[35] , which is a homogeneous catalyst so that MoC1-x/Cu-MgAlOx functions as both homogeneous and heterogeneous catalysts simultaneously. Hence, more radicals and ions were formed from ethanol with the MoC1-x/Cu-MgAlOx catalyst than that with Cu-MgAlOx as the catalyst.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Kraft lignin is waste produced during the utilization of lignocellulosic biomass in paper production [67]. Lignin is a complex and irregular macromolecule, constituting of mainly hydroxyphenyl propane and aliphatic chains [5,68].…”
Section: Ligninmentioning
confidence: 99%
“…Ma et al reported on the transformation of Kraft lignin into valuable chemicals over a molybdenum carbide catalyst in supercritical ethanol [67]. The products of reaction were a mixture of aliphatic alcohols, esters, monophenols, benzyl alcohols and arenes, with ester the predominant product (yield of 947 mg/g of lignin).…”
Section: Ligninmentioning
confidence: 99%